Why Asian Restaurants? An Exploratory Study of UK Customers’ Motivation to Visit - Jang, Seo Yeon (Advances in Social Sciences Research Journal, 2023)
The purpose of this study is to expand the understanding of Asian restaurants by examining customers’ motivation to visit Asian restaurants in the UK. This study adopted qualitative study approach and the results of semi-structured in-depth interviews revealed motivational attributes categorized into six motivational factors for customers to choose Asian restaurants: general attributes; sensory appeal-spiciness; variety and for change; curiosity; authenticity; and cultural experience. The overall study results suggested that how Asian restaurants enhance its experience to attract more customers and how destination management organization can cooperate.